Rescuing lethal phenotypes induced by disruption of genes in mice: a review of novel strategies - Lipták, N; Gál, Z; Biró, B; Hiripi, L; Hoffmann, O I (Physiological research, 2021)
Approximately 35 % of the mouse genes are indispensable for life, thus, global knock-out (KO) of those genes may result in embryonic or early postnatal lethality due to developmental abnormalities. Several KO mouse lines are valuable human disease models, but viable homozygous mutant mice are frequently required to mirror most symptoms of a human disease. The site-specific gene editing systems, the transcription activator-like effector nucleases (TALENs), Zinc-finger nucleases (ZFNs) and the clustered regularly interspaced short palindrome repeat-associated Cas9 nuclease (CRISPR/Cas9) made the generation of KO mice more efficient than before, but the homozygous lethality is still an undesired side-effect in case of many genes. The literature search was conducted using PubMed and Web of Science databases until June 30th, 2020. The following terms were combined to find relevant studies: "lethality", "mice", "knock-out", "deficient", "embryonic", "perinatal", "rescue". Additional manual search was also performed to find the related human diseases in the Online Mendelian Inheritance in Man (OMIM) database and to check the citations of the selected studies for rescuing methods. In this review, the possible solutions for rescuing human disease-relevant homozygous KO mice lethal phenotypes were summarized.
Keywords: Transcription Activator-Like Effector Nucleases; Mice; Embryo Loss; CRISPR-Cas Systems; myši knockoutované; TALENs; Gene Editing; ztráta embrya; Animals; CRISPR-Cas systémy; Phenotype; Mice, Knockout; editace genu; zvířata; fenotyp; myši; Zinc Finger Nucleases; nukleasy s motivem zinkových prstů